Basic Statistics using Excel 2007 - G. Marchal William (Mc Graw Hill, 2007)
Lind/14e is a perennial market best seller due to its comprehensive coverage of statistical concepts and methods delivered in a student friendly, step-by-step format. The text presents concepts clearly and succinctly with a conversational writing style. All statistical concepts are illustrated with solved applied examples immediately upon introduction. Self reviews and exercises for each section, and review sections for groups of chapters also support the student learning steps. Modern computing applications (Excel, Minitab, and MegaStat for Excel) are introduced, and the text maintains a focus on presenting statistics concepts as applied to business. The fourteenth edition continues as a 'students' text with increased emphasis on interpretation of data and results